1999
DOI: 10.1038/sj.bjc.6690737
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and gemcitabine activity in NSCLC cell lines and in primary cultures from human lung cancer

Abstract: Non-small-cell lung cancer (NSCLC) is considered one of the most chemoresistant tumours, and in a recent overview the pessimism about the absolute survival benefits from chemotherapy was underlined (Non-small Cell Lung Cancer Collaborative Group, 1995). In particular, the meta-analysis revealed a survival benefit of 10% at 1 year in a supportive care setting and an increased median survival of 1.5 months in patients treated with platinum-based chemotherapy regimens, thus emphasizing the need for new, effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 20 publications
(22 reference statements)
2
22
0
2
Order By: Relevance
“…For example, gemcitabine (2Ј,2Ј-difluoro-2Ј-deoxycytidine) is synergistic in vitro with cisplatin in non-small cell lung cancer cell lines and this interaction is most pronounced when gemcitabine precedes this drug (4,5). Similar results were obtained using PANC-1 and BxPc3 pancreatic cancer cells for which the most synergistic schedule is gemcitabine followed by cisplatin (6), whereas additive to slightly synergistic or antagonistic effects are observed with gemcitabine followed by topotecan, paclitaxel, and docetaxel in various non-small cell lung cancer cell lines (7)(8)(9).…”
Section: Introductionsupporting
confidence: 68%
“…For example, gemcitabine (2Ј,2Ј-difluoro-2Ј-deoxycytidine) is synergistic in vitro with cisplatin in non-small cell lung cancer cell lines and this interaction is most pronounced when gemcitabine precedes this drug (4,5). Similar results were obtained using PANC-1 and BxPc3 pancreatic cancer cells for which the most synergistic schedule is gemcitabine followed by cisplatin (6), whereas additive to slightly synergistic or antagonistic effects are observed with gemcitabine followed by topotecan, paclitaxel, and docetaxel in various non-small cell lung cancer cell lines (7)(8)(9).…”
Section: Introductionsupporting
confidence: 68%
“…Following combined treatment, we determined SfAB. The results obtained were defined according to the following criteria: SfAB = SfA Â SfB indicated an additive effect, SfAB < fAxSfB, a synergistic effect, and SfAB > SfA Â SfB, an antagonistic effect, as described (21).…”
Section: Methodsmentioning
confidence: 99%
“…Normal test was used to test for statistical significance of the differences in the arg and pro allele status, and only those with P < 0.05 were considered significant. To quantify deviations from additive effects induced by sequential treatment of two drugs, a statistical Student's test was employed, as described (21). For a given drug dose, we determined survival fraction (Sf) of cells: SfA for the first drug used in sequential schemes and SfB for the second.…”
Section: Methodsmentioning
confidence: 99%
“…Gemcitabine and docetaxel applied simultaneously to lung cancer cell lines were antagonistic with one another, and were somewhat less than additive when gemcitabine preceded paclitaxel or vice versa [33]. Zoli et al [34] showed that gemcitabine given before docetaxel was modestly synergistic in non-small cell lung cancer cell lines. Docetaxel given before gemcitabine (with a washout period) engendered significant synergy, perhaps from synchronizing the cell line to the effects of gemcitabine.…”
Section: Gemcitabine and Docetaxel: Possible Synergy?mentioning
confidence: 99%